Gold Nanoparticles Stabilized by Molecular Fullerenols. Issue 4 (6th March 2020) - Kokubo, Ken; Espejo Cabello, Mark Kristan; Sato, Nozomi; Uetake, Yuta; Sakurai, Hidehiro
Abstract: Polyhydroxylated fullerene derivatives (fullerenols: C60 (OH)12 and C60 (OH)36 ) exhibit excellent stabilizing matrices for gold nanoparticles. Au:C60 (OH)12 and Au:C60 (OH)36 form hydrophilic colloids and are well dispersed in H2 O, even though C60 (OH)12 itself is barely dissolved in H2 O. It was estimated that C60 (OH)12 forms a two‐ to three‐layered structure with 3D O−H⋅⋅⋅O hydrogen‐bonding networks, surrounding approximately 3 nm‐sized Au NPs. The thus‐prepared Au:C60 (OH)n colloids exhibited a high catalytic activity toward the reduction of 4‐nitrophenol to 4‐aminophenol. The short induction period as well as kinetic and thermodynamic parameters indicated the dynamic mobility of the fullerenol matrix and the hydrophobic nature of the interface between the Au surface and the matrix. Abstract : Gold nanoparticles stabilized by fullerenols matrices (C60 (OH)n ) have been prepared. The thus‐prepared nanocomposites (Au:C60 (OH)12 and Au:C60 (OH)36 ) formed hydrophilic colloids, which can disperse well in H2 O. The short induction period, and kinetic and thermodynamic parameters on the reduction of 4‐nitrophenol indicated the dynamic mobility of the fullerenol matrix and the hydrophobic nature of the interface between the Au surface and fullerenols.